Demokrasi dan Syura: Persepektif Islam dan Barat - Muhammad Ichsan (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2014)
In this globalization era, the term of democracy has been part of political culture in Muslim society, which unintentionally hindered the term of syura as Muslim political reference. In fact, that democracy and syura are two different concepts in Islamic discourses. The concept of democracy, which is understood, developed and introduced by West to Muslim, is not very applicable in Muslim world. It is because the whole concept of western democracy unlikely relevant with Quran and Prophet Tradition. Western democracy, for instance, positions people as the owner of the highest sovereignty. It means that whatever the people’s words, they will be treated as a truth, although they might be wrong. While syura, as Muslim political reference, perceives Allah as the owner of the highest sovereignty. Humankind is commanded to apply the concept. If Muslims are going to apply any political will, they must firstly consult to the Quran and Sunnah whether the will is applicable or not.Abstrak: Kata demokrasi di era globalisasi dewasa ini sudah membudaya dan dipraktekkan dalam kehidupan masyarakat muslim, sehingga kata syura yang merupakan acuan umat Islam dalam menjalankan kehidupan dalam masyarakat hampir dilupakan. Padahal antara demokrasi dan syura terdapat perbedaan dalam kajian Islam. Demokrasi yang dipahami dan dikembangkan oleh dunia barat kepada dunia Islam tidak semuanya dapat diterima dan diterapkan di dunia Islam, karena banyak hal yang terkadang tidak sesuai dengan ketentuan-ketentuan yang telah digariskan dalam al-Qur’an dan Sunnah Rasulullah Saw. Misalnya kalau demokrasi yang dipahami barat kedaulatan tertinggi berada di tangan rakyat, apa yang dikatakan oleh rakyat itulah yang benar walaupun terkadang hal tersebut tidak benar. Sedangkan dalam Islam, kedaulatan tertinggi berada di tangan Allah Swt, manusia hanya diberikan amanah untuk melaksanakannya saja. Bila ada hal-hal yang ingin dilakukan, maka harus dikembalikan kepada al-Qur’an dan Sunnah untuk mengetahui ketentuan apakah boleh dilaksanakan ataupun tidak.